FACTORS, METHODS AND MEANS OF IMPROVING YOUTH'S ECOLOGICAL AWARENESS AND CULTURE - Agzamova Zumrad (Bright Mind Publishing, 2025)
This article examines the key factors, effective pedagogical approaches, and modern methods and tools involved in shaping and enhancing ecological awareness and culture among the younger generation. It explores how integrated approaches within the educational process can be utilized to foster environmental education and strengthen students' sense of social responsibility toward ecological issues. Furthermore, the study analyzes the collaborative efforts of families, general education institutions, mass media, and civil society organizations in promoting environmental culture. Special attention is given to the application of interactive teaching methods, information and communication technologies, and innovative educational tools, emphasizing their role in cultivating sustainable ecological values in youth. The findings of the research present scientifically grounded and practically oriented recommendations aimed at increasing youth engagement in ensuring environmental safety and achieving sustainable development goals.
Keywords: Youth, ecological consciousness, environmental culture, environmental education, sustainable development, pedagogical methods, interactive approaches, innovative technologies, environmental safety, information and communication tools.